The Effect of Sales Promotion and Shopping Lifestyle on Impulse Buying with Positive Emotion as a Mediating Variable for Shopee Customers in Pekanbaru City - Gatot Wijayanto; Arwinence Pramadewi; Jushermi; Aulya Anindita Pratiwi; Muhammad Syafi’i (Jurnal Multidisiplin Madani, 2023)
This study aims to determine the effect of sales promotion and shopping lifestyle on impulse buying with positive emotion as a mediating variable for shopee customers in Pekanbaru City. The analytical approach uses quantitative methods by collecting data using survey methods. The population in this study were online service users at the Shoppe market place in the city of Pekanbaru. The number of samples taken in this study were 100 respondents. The sampling technique used in this study was accidental sampling. The results showed that Sales Promotion (X1) had a significant effect on Positive Emotion (M), Shopping Lifestyle (X2) had a significant effect on Positive Emotion (M), Sales Promotion (X1) had a significant effect on Impulse Buying (Y), Shopping Lifestyle (X2) ) has a positive and significant effect on Impulse Buying (Y), Positive Emotion (M) has a positive and significant effect on Impulse Buying (Y), Sales Promotion (X1) has a significant effect on Impulse Buying (Y) through Positive Emotion (M), and Shopping Lifestyle (X2) has a positive and significant effect on Impulse Buying (Y) through Positive Emotion (M)